توظيف الوسائط المتعددة (تقنية المعلومات والاتصالات وأدوات التواصل الاجتماعي) في التعليم والتعلم - Chik, Abdul Rahman (2015)
Applying multi media technology (ICT and Social media) in teaching and learning.